2015
DOI: 10.1016/j.bbamcr.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-dependence of breast cancer cell types on the nuclear transporter Importin β1

Abstract: We previously reported that overexpression of members of the Importin (Imp) superfamily of nuclear transporters results in increased nuclear trafficking through conventional transport pathways in tumour cells. Here we show for the first time that the extent of overexpression of Impβ1 correlates with disease state in the MCF10 human breast tumour progression system. Excitingly, we find that targeting Impβ1 activity through siRNA is >30 times more efficient in decreasing the viability of malignant ductal carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Of note, importin β1knockdown led to relocalization of Cat L from the nucleus to the cytoplasm in MDA-MB-468 cells, while it led to decreased Cat L expression in MCF-7 Snail cells, which highlights cell line differences but does not detract from the overall theme. Another noteworthy observation was that Snail overexpression increased importin β1 expression; this supports a report that more aggressive breast cancer cells overexpress importin β1, where it was further shown that importin β1 silencing was more potent in malignant compared to non-transformed breast cancer cells [15]. It has also been shown that importin β1is overexpressed in cervical cancer and inhibition with siRNA inhibited tumor cell proliferation without affecting normal cervical epithelium [16].…”
Section: Discussionsupporting
confidence: 72%
“…Of note, importin β1knockdown led to relocalization of Cat L from the nucleus to the cytoplasm in MDA-MB-468 cells, while it led to decreased Cat L expression in MCF-7 Snail cells, which highlights cell line differences but does not detract from the overall theme. Another noteworthy observation was that Snail overexpression increased importin β1 expression; this supports a report that more aggressive breast cancer cells overexpress importin β1, where it was further shown that importin β1 silencing was more potent in malignant compared to non-transformed breast cancer cells [15]. It has also been shown that importin β1is overexpressed in cervical cancer and inhibition with siRNA inhibited tumor cell proliferation without affecting normal cervical epithelium [16].…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, Kuusisto and Jans identified a so-called hypersensitivity of malignant cell types towards the inhibition of the nuclear import receptor importin β. 62 Moreover, as mentioned earlier, the overexpression of nuclear transport receptors in cancer cells indicates an increased dependence of cancer cells on specific proteins which is referred to as tumor cell addiction. 63 In consequence, 3D tumor spheroids show great potential for studying the HIF-dependent hypoxic response and should be considered in future research.…”
Section: Dovepressmentioning
confidence: 95%
“…The E2F/Rb pathway is disrupted in a remarkably high proportion of human cancers through other mechanisms leading to the same overexpression phenotype . Interestingly, Kuusisto et al showed that the extent of overexpression of KPNB1 correlates with disease state in the MCF10 human breast tumour progression system, suggesting that its overexpression not only correlates with E2F dysregulation but can vary according to tumour progression state . Other mechanisms for altered Karyopherin expression have been reported.…”
Section: Dysregulation Of Nuclear Transport In Cancermentioning
confidence: 99%
“…Challenges may arise though when targeting cellular machinery that is active in both normal and cancer cells. However, studies have shown that cancer cells are more sensitive to nuclear transport inhibition than non‐cancer cells which remain viable ( 3 , ). Specific knockdown using siRNA for nuclear import proteins, KPNB1 and KPNA2, and export proteins, XPO1 and CSE1L, in cancer cells frequently results in reduced proliferation and increased apoptosis .…”
Section: Targeting Nuclear Transporters As Cancer Therapeuticsmentioning
confidence: 99%